The Evoked Compound Action Potential as a Predictor for Perception in Chronic Pain Patients: Tools for Automatic Spinal Cord Stimulator Programming and Control - Pilitsis, Julie G.; Chakravarthy, Krishnan V.; Will, Andrew J.; Trutnau, Karen C.; Hageman, Kristin N.; Dinsmoor, David A.; Litvak, Leonid M. (Frontiers in Neuroscience, 2021)
Objectives: Spinal cord stimulation (SCS) is a drug free treatment for chronic pain. Recent technological advances have enabled sensing of the evoked compound action potential (ECAP), a biopotential that represents neural activity elicited from SCS. The amplitudes of many SCS paradigms—both sub- and supra-threshold—are programmed relative to the patient’s perception of SCS. The objective of this study, then, is to elucidate relationships between the ECAP and perception thresholds across posture and SCS pulse width. These relationships may be used for the automatic control and perceptually referenced programming of SCS systems. Methods: ECAPs were acquired from 14 subjects across a range of postures and pulse widths with swept amplitude stimulation. Perception (PT) and discomfort (DT) thresholds were recorded. A stimulation artifact reduction scheme was employed, and growth curves were constructed from the sweeps. An estimate of the ECAP threshold, ET, was calculated from the growth curves using a novel approach. Relationships between ET, PT, and DT were assessed. Results: ETs were estimated from 112 separate growth curves. For the postures and pulse widths assessed, the ET tightly correlated with both PT (r=0.93; P < 0.0001) and DT (r=0.93; P < 0.0001). The median accuracy of ET as a predictor for PT across both posture and pulse width was 0.5 dB. Intra-subject, ECAP amplitudes at DT varied up to threefold across posture. Conclusions: We provide evidence that the ET varies across both different positions and varying pulse widths and suggest that this variance may be the result of postural dependence of the recording electrode-tissue spacing. ET-informed SCS holds promise as a tool for SCS parameter configuration and may offer more accuracy over the ECAP amplitude alone for neural and perceptual control in closed loop SCS systems.